BETWEEN PRESTIGE AND DEPRAVITY: OBSERVATIONS ON THE EARLY RECEPTION OF DANTE AND BOCCACCHIO IN BULGARIA (1878 – 1918) - Boyka Ilieva (Езиков свят)
The current study focuses on the presence of the Italian classic authors Dante, Petrarch and Boccaccio in the period from the National Liberation to the end of World War I. The reception scope after the National Liberation is actually hard to trace and some surprising findings might appear on the horizon, especially regarding the scattered in periodicals texts. The published translated books are not indicative of the reception range during the analyzed period and they constitute only a small part of it. A large number of works by the most popular authors reached the Bulgarian audience through translations published in periodicals, textbooks and anthologies. Moreover, a lot of translated works did not appear in specialized philological publications, but in the literary sections and serials of daily newspapers. As early as the first decade after the Liberation, the classics missing from the Revival catalogue of translated literature started to appear. The Bulgarian reader became acquainted with the sporadic works of authors studied at school like Dante, Petrarch, Boccaccio, Torquato Tasso, Ludovico Ariosto, Carlo Goldoni, Vittorio Alfieri, Giacomo Leopardi and Ugo Foscolo. In the defined period, the classic authors were not among the most influential translated Italian writers for the Bulgarian audience during the epoch. This is evidenced by the limited distribution of Konstantin Velichkov’s translation of Inferno, which managed to attract the interest of only a small circle of intellectuals. A main reception factor is the taste of the reading audience, which predominantly in the postliberation conditions still lacked structured esthetic criteria and preferred more common and comprehensible literature.